2019
DOI: 10.1038/s41467-019-11661-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep multiomics profiling of brain tumors identifies signaling networks downstream of cancer driver genes

Abstract: High throughput omics approaches provide an unprecedented opportunity for dissecting molecular mechanisms in cancer biology. Here we present deep profiling of whole proteome, phosphoproteome and transcriptome in two high-grade glioma (HGG) mouse models driven by mutated RTK oncogenes, PDGFRA and NTRK1 , analyzing 13,860 proteins and 30,431 phosphosites by mass spectrometry. Systems biology approaches identify numerous master regulators, including 41 kinases and 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 70 publications
2
34
0
Order By: Relevance
“…We found that JUN played role in four CNV patterns, and MYC in CNV patterns 2, 3 and 4, while TP53 and E2F1 were specific to CNV pattern 1, SMAD2 specific to CNV patterns 3, and FOS specific to CNV pattern 4 (Figure 3B, C). Similarly, Hong Wang and colleagues also identified JUN and MYC as centered TFs in high-grade glioma (HGG) mouse models by combinatory profiling of proteome, phosphoproteome, and transcriptome 29 , which proved the effectiveness of our analysis strategy. On the other hand, we identified differentially expressed TFs and TCFs with fold changes larger than two compared to normal cells.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…We found that JUN played role in four CNV patterns, and MYC in CNV patterns 2, 3 and 4, while TP53 and E2F1 were specific to CNV pattern 1, SMAD2 specific to CNV patterns 3, and FOS specific to CNV pattern 4 (Figure 3B, C). Similarly, Hong Wang and colleagues also identified JUN and MYC as centered TFs in high-grade glioma (HGG) mouse models by combinatory profiling of proteome, phosphoproteome, and transcriptome 29 , which proved the effectiveness of our analysis strategy. On the other hand, we identified differentially expressed TFs and TCFs with fold changes larger than two compared to normal cells.…”
Section: Resultsmentioning
confidence: 65%
“…In particular, the core TFs-TCFs gene set of CNV pattern 4 was negatively correlated with both OS and PFS of GBM patients. Despite prominent heterogeneity, we figured out some common TFs among four CNV patterns, such as JUN and MYC, which were also identified as central TFs by recently published study using multiomics to construct kinase-TF centered network in HGG 29 .…”
Section: Discussionmentioning
confidence: 85%
“…PCA is commonly used to segregate groups of samples or explore origins of variance in a dataset. 41 , 42 Veling et al used PCA (2B) to demonstrate clear separation between the respiration-deficient and respiration-competent deletion strains. Biomolecule abundance correlation analysis is often used in gene deletion experiments to (2C) demonstrate a functional relationship between two gene deletion strains.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wang et al identified signaling networks downstream of cancer driver genes in brain tumors by multi‐omics profiling. [ 158 ] It has been shown that pathways are more relevant than individual genes to cancer progression, [ 159 ] which makes it worth studying mutations at pathway level. Identification of multi‐omics signatures of GBM has also allowed to establish prognostic subtypes, namely invasive (poor), mitotic (favorable), and intermediate.…”
Section: Clinical Management Of Glioblastoma: New Diagnosis Opportunimentioning
confidence: 99%